Co-aggregation of pro-inflammatory S100A9 with α-synuclein in Parkinson’s disease: ex vivo and in vitro studies - István Horváth; Igor A. Iashchishyn; Roman Moskalenko; Chao Wang; Sebastian K.T.S. Wärmländer; Cecilia Wallin; Astrid Gräslund; Gábor G. Kovács; Ludmilla A. Morozova‐Roche (2018)
Chronic neuroinflammation is a hallmark of Parkinson's disease (PD) pathophysiology, associated with increased levels of pro-inflammatory factors in PD brain tissues. The pro-inflammatory mediator and highly amyloidogenic protein S100A9 is involved in the amyloid-neuroinflammatory cascade in Alzheimer's disease. This is the first report on the co-aggregation of α-synuclein (α-syn) and S100A9 both in vitro and ex vivo in PD brain. Single and sequential immunohistochemistry, immunofluorescence, scanning electron and atomic force (AFM) microscopies were used to analyze the ex vivo PD brain tissues for S100A9 and α-syn location and aggregation. In vitro studies revealing S100A9 and α-syn interaction and co-aggregation were conducted by NMR, circular dichroism, Thioflavin-T fluorescence, AFM, and surface plasmon resonance methods. Co-localized and co-aggregated S100A9 and α-syn were found in 20% Lewy bodies and 77% neuronal cells in the substantia nigra; both proteins were also observed in Lewy bodies in PD frontal lobe (Braak stages 4–6). Lewy bodies were characterized by ca. 10–23 μm outer diameter, with S100A9 and α-syn being co-localized in the same lamellar structures. S100A9 was also detected in neurons and blood vessels of the aged patients without PD, but in much lesser extent. In vitro S100A9 and α-syn were shown to interact with each other via the α-syn C-terminus with an apparent dissociation constant of ca. 5 μM. Their co-aggregation occurred significantly faster and led to formation of larger amyloid aggregates than the self-assembly of individual proteins. S100A9 amyloid oligomers were more toxic than those of α-syn, while co-aggregation of both proteins mitigated the cytotoxicity of S100A9 oligomers. We suggest that sustained neuroinflammation promoting the spread of amyloidogenic S100A9 in the brain tissues may trigger the amyloid cascade involving α-syn and S100A9 and leading to PD, similar to the effect of S100A9 and Aβ co-aggregation in Alzheimer's disease. The finding of S100A9 involvement in PD may open a new avenue for therapeutic interventions targeting S100A9 and preventing its amyloid self-assembly in affected brain tissues.